IT and the Indian legal system/edited by Kamlesh N. Agarwala and Murti D. Tiwari - "Tiwari, Murli D.(ed.)" (New Delhi, 2002)
This collection of articles shows how the Indian legal system can be transformed into a proactive legal redressal system. The challenges posed by cyber crime, the possibilities of e-enabled legal profession and the ramifications of cyber law on jurisprudential science and its repercussions on Indian courts are also discussed.
Keywords: Information technology